Flow equations for Yang-Mills theories in general axial gauges - Litim, Daniel F.; Pawlowski, Jan M. (Arxiv, 1998)
We present a formulation of non-Abelian gauge theories in general axial gauges using a Wilsonian (or 'Exact') Renormalisation Group. No 'spurious' propagator divergencies are encountered in contrast to standard perturbation theory. Modified Ward identities, compatible with the flow equation, ensure gauge invariance of physical Green functions. The axial gauge